1970. Phase 1 Clinical Trial of Intranasal Immunization with M2-Deficient, Single Replication, Live Influenza Vaccine (M2SR): Safety and Immune Response in Adults. (26th November 2018) - Eiden, Joseph; Gordon, Gilad; Fierro, Carlos; Belshe, Robert; Greenberg, Harry; Hoft, Dan; Hatta, Yasuko; Imboden, Michael; Moser, Mike; Herber, Renee; Boltz, David; Tary-Lehmann, Magdalena; et al.
Abstract: Background: Influenza vaccines are needed with greater effectiveness and breadth of coverage. FluGen is developing M2SR ( M2 deficient S ingle R eplication), an investigational, live virus vaccine. M2SR contains the internal proteins of donor A/Puerto Rico/8/34 and hemagglutinin (HA) and neuraminidase (NA) selected from targeted Type A influenza strains. M2SR undergoes only a single round of infection in the respiratory epithelium but evokes an immune response profile similar to wild-type influenza viruses. In influenza naïve and pre-immune ferrets, M2SR protects against multiple influenza A subtypes. Methods: A Phase 1, first-in-human, randomized, placebo-control study (FluGen-H3N2-V001; ClinicalTrials.gov identifier NCT02822105) was conducted at a single USA site, with 96 adults, ages 18–49 years. Study vaccine contained HA and NA from A/Brisbane/10/2007 (H3N2). Study volunteers received a single intranasal (IN) inoculation with either M2SR at dose levels of 10 6, 10 7 or 10 8 TCID50 or saline placebo ( N = 24/cohort). Study subjects were evaluated for virus replication and solicited local and systemic reactions for 7 days, all adverse events (AE) for 28 days and serious AE (SAE) for 180 days. Results: No infectious virus was detected in nasal swabs from any vaccinated subject. The most commonly reported AE was mild nasal rhinorrhea/congestion during the first 7 days after vaccination (Figure 1). No subject had fever or a severe reaction to the vaccine. No SAEs were reported. At least one AE was reported among 29%, 58%, and 83% of M2SR subjects administered 10 6, 10 7, or 10 8 TCID50, respectively, and 46% among placebo subjects. There were no notable imbalances among study groups for other events. T- and B-cell responses, including influenza-specific serum and mucosal antibody responses were detected at a significantly higher frequency among vaccine than placebo subjects (Figure 2). Conclusion: M2SR vaccine was safe and well tolerated at all dose levels, generated a dose-response effect for humoral (HA antibody) and mucosal antibodies against both homologous and heterologous influenza variants, and elicited robust T-cell responses. No infectious virus was detected in nasal swabs from any vaccinated subject. Disclosures: J. Eiden, FluGen, Inc.: Consultant, Consulting fee and Stock Options. G. Gordon, FluGen: Consultant, Consulting fee. C. Fierro, FluGen: Investigator, Fee for service. R. Belshe, FluGen: Consultant, Consulting fee and Stock Options. H. Greenberg, FluGen: Consultant, Consulting fee and Stock OpTions. D. Hoft, FluGen: Research Contractor, Fee for service. Y. Hatta, FluGen: Employee, Salary and Stock Options. M. Imboden, FluGen: Employee, Salary and Stock Options. M. Moser, FluGen: Employee, Salary and Stock Options. R. Herber, FluGen: Employee, Salary and Stock Options. D. Boltz, FluGen: Research Contractor, fee for service. M. Tary-Lehmann, FluGen: Research Contractor, Fee for service. CTL: Founder and Owner, Salary. Y. Kawaoka, FluGen: Founder, Stock Options. G. Neumann, FluGen: Founder, Stock Options. P. Radspinner, FluGen: Board Member and Founder, Salary and Stock Options. R. Aitchison, FluGen: Consultant, Consulting fee. P. Bilsel, FluGen: Employee, Salary and Stock Options.